ROBUSTNESS OF GENERALLY WEIGHTED MOVING AVERAGE SIGNED – RANK CONTROL CHART FOR MONITORING A SHIFT OF SKEW PROCESSES - Sukparungsee, Saowanit (MATTER: International Journal of Science and Technology, 2018)
A distribution-free control charts play a virtual role in quality control chart because it is not necessary to know the assumption of specific distribution for any process. In this article, the robustness of a generally weighted moving average based on signed-rank (GWMA-SR) control charts are intensive studied for skew processes. In addition, the GWMA-SR control chart is compared the performance to detecting a shift in process mean based on GWMA with sign statistic (GWMA-SN) and exponentially weighted moving average with signed-rank statistic (EWMA-SR) control charts. The numerical results using Monte Carlo simulation found that the performance of GWMA-SR chart robust to skew process and perform as good as the benchmark charts. Furthermore, the GWMA-SR chart is superior to existing chart in many situations.